A new braking torque distribution strategy based on braking actuator characteristics and a command signal for a blended braking system. Issue 6 (1st March 2022) - Li, Wenfei; Li, Huiyun; Huang, Zhejun; Liu, Jia; Dang, Shaobo; Du, Haiping
Abstract: Braking torque distribution strategy is not only related to the tracking performance of the blended braking system in commanding the braking signal, but is also related to the energy utilization efficiency of the blended braking system. In this paper, a new braking torque distribution strategy is designed for a blended braking system consisting of a motor braking system and a friction braking system. In contrast to the classic braking torque distribution strategy, which adjusts the braking torque distribution ratio based on the braking strength, the newly designed braking torque distribution strategy adjusts the braking torque that is allocated to the motor braking system and friction braking system, according to the command braking torque signal, the braking actuators' dynamic characteristics and the motor's electrical characteristics. In addition, a three‐layer controller is designed to ensure the execution of the proposed braking torque distribution strategy and the stability of the blended braking system. Compared to the classic distribution strategy, based on braking strength, numerical simulation results show that the braking energy recovery of the blended braking system has been improved by 16% in normal braking conditions and has been improved by 84% in emergency braking conditions under the new braking torque distribution strategy.